PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 24 KUALA PENASO - Rini Astika; Erlisnawati Erlisnawati; Syahrilfuddin Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem this research is the student achievement of social studies fifth graderes SDN 24 Kuala Penaso still low with an average value of 58,66 and minimum completenness criteria (KKM) social studies is 65. Between students, amounting to 15 people only 6 students who achieve classical KKM with 40%. This research is Classroom action Research (CAR), wich aims to improve the learning process in the classroom. Formulation of the problem : is the implementation of direct learning model can improve students achievment of social studies at SDN 24 Kuala Penaso. The research was conducted on march 10 2015 to 24 march 2015 by 2 cyclees. Subjects were students of SDN 24 Kuala Penaso, totalling 15 people who use the data source. The data collection instruments in this research is a teacher and students activities sheets and students achievement. Based on the conduct of research with the implementation of direct learning models obtained results direct type of activity the teacher in the lerning process in cycle I frist meeting was 65% and at the second meeting of teacher activity increased by 15% to 80%. cycle II firs meeting and the second meeting of activity increased by 5% to 85% and the second meeting of activity increased by 10% to 95%. Result of data analysis of students activities in the first meeting cycle with the first meeting of an avarage of 65% and at second meeting of activity increased 10% to 75%% and a second meeting of activity increased 5% improve to 80%. At the firs meeting of the second meeting of activity increased 10% to 90%. This research presents the results obtained each before the implementation an improve in base score sycle with the average being, 58,66. In the first cycle improve an average of 76 with increase as 29,56% and an impove in the second with an average of 86 with increase as 46,60%. Result in the research that the implementation of cooperative learning model of direct can improve students achievement of social Studies at fifth graderes SDN 24 Kuala Penaso.Key Words : Model Direct Learning, Fave graderes students Achievement